The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s10439-009-9826-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Focal Adhesion Proteins on Endothelial Cell Adhesion, Motility and Orientation Response to Cyclic Strain

Abstract: Focal adhesion proteins link cell surface integrins and intracellular actin stress fibers and therefore play an important role in mechanotransduction and cell motility. When endothelial cells are subjected to cyclic mechanical strain, time-lapse imaging revealed that cells underwent significant morphological changes with their resultant long axes aligned away from the strain direction. To explore how this response is regulated by focal adhesion-associated proteins the expression levels of paxillin, focal adhes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 35 publications
2
49
0
Order By: Relevance
“…Vimentin-GFP-transfected cells fixed and stained for vinculin-rich FAs (Figure 3), reveal that elongated cells (Figure 3(a)) had fewer FAs than flat cells (Figure 3(b)). This results in an inability to transmit forces from the FAs into the CSK [25]. It has also been postulated that fibroblast cells of this morphology have lower substrate-adhesion (which is consistent with our study) [26].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Vimentin-GFP-transfected cells fixed and stained for vinculin-rich FAs (Figure 3), reveal that elongated cells (Figure 3(a)) had fewer FAs than flat cells (Figure 3(b)). This results in an inability to transmit forces from the FAs into the CSK [25]. It has also been postulated that fibroblast cells of this morphology have lower substrate-adhesion (which is consistent with our study) [26].…”
Section: Resultssupporting
confidence: 91%
“…It was observed that elongated cells have far fewer FAs than flat adherent cells. Thus it thought to reduce cell attachment to the substrate [25,26], which, combined with the reduced Young's Modulus of the elongated cells, allows for increased deformation of the IF CSK.…”
Section: Discussionmentioning
confidence: 99%
“…Because previous studies have shown that cyclic tensile forces can affect orientation at the endothelial cellular level (27,28), we now set out to also examine their effect on vessel network morphology and orientation. To this end, 3D Gelfoam scaffolds cocultured with ECs and fibroblasts for 4 d were exposed to uniaxial cyclic stretching (10% strain and 1-Hz frequency).…”
Section: Static Tensile Forces Influence Vascular Network Organizatiomentioning
confidence: 99%
“…In the previous studies, the carcinogenesis of human CRC is related to the FAK destabilization [3,10,11] . By treatment of lactate-bound Ca 2+ , the full length of FAK is cleaved into a 90 kDa N-FAK protein (FERM domain).…”
Section: Research Highlightmentioning
confidence: 98%